Combining Activism and Intellectualism: the Biography of Mohammad Natsir (1908-1993) - Mahendra, Yusril Ihza (Studia Islamika, 1995)
Mohammad Natsir is one of Indonesia's leading Islamic figures of the century. His figure is not only known by the people of Indonesia, but also by the world community, especially the Islamic world. Throughout his life, Natsir actively involved in various movements, whether they are social, political, scientific, and religious.Aside from being a powerful activist, Natsir also a respected intellectual figure. Through interaction with Ahmad Hassan, Agus Salim, and other figures, Natsir have started engaging intellectual debate since adolescence. Natsir wrote many articles in the fields of political, social, religious, and philosophical. He also became one of the principal framers of the relationship between religion and the state in Indonesia. Unlike the secular Muslims, Natsir continue to believe that Islam could be the basis of the state. Meanwhile, different from the Muslim protagonist, Natsir also believe that Islam does not have a particular political system preferences. Islam only provide general principles to be applied in a particular political system that is tailored to the situation and his time. Thus, Islam and Pancasila still can go hand in hand, because of the unity between Islam and Pancasila occurs at the level of ideas.DOI: 10.15408/sdi.v2i1.844